1996
DOI: 10.1128/aac.40.5.1219
|View full text |Cite
|
Sign up to set email alerts
|

Importance of penicillinase production for activity of penicillin alone or in combination with sulbactam in experimental endocarditis due to methicillin-resistant Staphylococcus aureus

Abstract: The activity of penicillin, alone and in combination with sulbactam, against a heterogeneously methicillin-resistant, penicillinase-producing clinical isolate of Staphylococcus aureus and its penicillinase-negative derivative was investigated in vitro and in a rabbit experimental endocarditis model. Penicillin was significantly more effective than vancomycin against the penicillinase-negative derivative in vivo (P < 0.001), and it sterilized 25% of the vegetations. The combination of penicillin and sulbacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Although vancomycin is considered the best agent in this model, it is relatively ineffective at sterilizing aortic valve vegetations, results that mirror the lack of efficacy reported for vancomycin therapy of human S. aureus endocarditis. Of 15 studies of experimental MRSA aortic valve endocarditis with vancomycin doses and treatment durations similar to those used in our study, 6 reported no sterilization of aortic valve vegetations (5,7,13,16,18,19), while 4 described sterilization of fewer than half of the vegetations (1,6,10,32). Five remaining studies (11,14,(26)(27)(28) reported aortic valve sterilization rates of 55 to 87%, although three of those studies used an MRSA strain that appears to have been more easily eradicated by a variety of antimicrobial agents in this model (26)(27)(28).…”
Section: Discussionmentioning
confidence: 69%
“…Although vancomycin is considered the best agent in this model, it is relatively ineffective at sterilizing aortic valve vegetations, results that mirror the lack of efficacy reported for vancomycin therapy of human S. aureus endocarditis. Of 15 studies of experimental MRSA aortic valve endocarditis with vancomycin doses and treatment durations similar to those used in our study, 6 reported no sterilization of aortic valve vegetations (5,7,13,16,18,19), while 4 described sterilization of fewer than half of the vegetations (1,6,10,32). Five remaining studies (11,14,(26)(27)(28) reported aortic valve sterilization rates of 55 to 87%, although three of those studies used an MRSA strain that appears to have been more easily eradicated by a variety of antimicrobial agents in this model (26)(27)(28).…”
Section: Discussionmentioning
confidence: 69%
“…Limits of quantification were 0.1 mg/liter and 0.1 mg/kg for plasma and lung samples, respectively. The method for dosing sulbactam was adapted from the technique reported by Fantin et al (8). Plasma and lung sulbactam levels were determined by RP-HPLC with UV detection at 313 nm.…”
Section: Methodsmentioning
confidence: 99%
“…These toxins include cytotoxins such as the 33-kDa K-toxin [6,7] and leukocytolytic toxins [8], exfoliative toxins including epidermolytic toxins A and B [9], pyrogenic superantigens such as enterotoxins [4,10] and toxic shock syndrome toxin (TSST-1) [10,11], and protein A [7,12]. Extracellular enzymes include lipase [13], hyaluronidase [14,15], coagulase [16], acid and alkaline phosphatases [17], penicillinase [18], nu-clease [19], staphylokinase [20] and various other proteases [3,21]. Most other staphylococcal exoproteins have not been well characterized yet.…”
Section: Introductionmentioning
confidence: 99%